Effect of different pressure on densification of sintered parts / Abdul Rahman Mat Saed - Mat Saed, Abdul Rahman (2005)
Pressure during compaction is the most important parameter in powder metallurgy application since it contributes to the physical and mechanical property of the part. This study attempts to investigate the effect of different compaction pressure on densification of sintered part and the characterization of ceramic powder in term of flow rate and powder packing density were included. Two types of ceramic powders were used in this study; alumina 9620 with 3% of acrylic binder denoted as NM 9620 and alumina 99 with 4% of acrylic binder denoted as NM99. Experimental works were carried out for a simple cylindrical die of compacted powder using a conventional compaction machine at room temperature. In this study, 5 compaction pressure levels were applied; 2, 4, 6, 8 and 10 tons then undergo sintering process at 1620°C and further investigation was made in term of density and dimensional changes. This provides information on the characterization of powder, compacted or green density and sintered density that been achieved from the ceramic powders used. It clearly shows that increasing compaction pressure result in increasing both densities of green and sintered part. It is shown by additional volume fraction of the binder result in greater shrinkage. In characterization of ceramic powder, smaller particle size offers higher flow rate and tap density but lesser in apparent density. Spherical particles despite their high apparent densities have poor compaction properties due to weak bonding among them.